Effect of template type on the preparation of the emeraldine salt form of polyaniline (PANI-ES) with horseradish peroxidase isoenzyme C (HRPC) and hydrogen peroxide. Issue 57 (16th October 2019) - Fujisaki, Tomoyuki; Kashima, Keita; Serrano-Luginbühl, Sandra; Kissner, Reinhard; Bajuk-Bogdanović, Danica; Milojević-Rakić, Maja; Ćirić-Marjanović, Gordana; Busato, Stephan; Lizundia, Erlantz; Walde, Peter
Abstract : Different types of templates consisting of sulfonate or sulfate groups were compared for the horseradish peroxidase/H2 O2 -catalysed synthesis of the emeraldine salt form of polyaniline from aniline at pH = 4.3. Abstract : Horseradish peroxidase isoenzyme C (HRPC) is often used as catalyst for the preparation of the conductive emeraldine salt form of polyaniline (PANI-ES) from aniline and hydrogen peroxide (H2 O2 ) in the presence of anionic templates in aqueous solution. Here, a direct comparison of three types of soft templates was made, (i) the sodium salt of sulfonated polystyrene (SPS), (ii) micelles from sodium dodecylbenzenesulfonate (SDBS), and (iii) vesicles from either a 1 : 1 molar mixture of SDBS and decanoic acid or from AOT (sodium bis(2-ethylhexyl)sulfosuccinate). Based on UV/vis/NIR, EPR and Raman spectroscopy measurements all three types of templates are similarly suitable, with advantages of the two vesicle systems in terms of aniline conversion degree and radical content in the final PANI-ES product. First experiments with sulfated cellulose nanocrystals (CNCs) indicate that they are promising rigid templates for the preparation of electroconductive PANI-ES-coated cellulose materials or devices.